Shearing stress of shoaling internal solitary waves over the slope. (1st December 2021) - Tian, Zhuangcai; Jia, Yonggang; Du, Qizhi; Zhang, Shaotong; Guo, Xiujun; Tian, Wenwen; Zhang, Mingwei; Song, Lei
Abstract: The interaction between internal solitary waves (ISWs) and the seabed has been extensively studied, so do the energy loss, sediment resuspension, parameterization criterion and near-bed pressure variation. However, the horizontal and vertical shearing stresses of ISWs have not been directly measured. In this paper, flume experiments were designed to examine the near-bed pressure variation of shoaling ISWs over the slope with a novel device possessing four pressure sensors in different directions. Then the vertical and horizontal shearing stresses of ISWs were analyzed, with the shearing stress of ISWs in the South China Sea predicted based on field observation. The results showed that the maximum pressure variation of shoaling ISWs approximated 20 Pa, with the ISWs' horizontal shearing stress, about 3–6 Pa and the vertical one, about 10 Pa. It was predicted that the horizontal and vertical shearing stresses of ISWs in the open ocean were 5–100 kPa, larger than the maximum critical shearing stress of the sediment. This paper could promote the understanding of the seabed damage caused by ISWs and is expected to provide a reference for future field experiment design for the direct interaction measurement between ISWs and seabed sediments. Highlights: The horizontal and vertical shearing stresses of internal solitary waves were directly measured in the flume. The horizontal and vertical shearing stresses of internal solitary waves in the open ocean are predicted 5–100 kPa. The horizontal and vertical shearing stresses of internal solitary waves in open ocean were larger than the maximum critical shearing stress of sediment.